2015
DOI: 10.1371/journal.pone.0127831
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an AP2/ERF Type Transcription Factor OsEREBP1 Confers Biotic and Abiotic Stress Tolerance in Rice

Abstract: AP2/ERF–type transcription factors regulate important functions of plant growth and development as well as responses to environmental stimuli. A rice AP2/ERF transcription factor, OsEREBP1 is a downstream component of a signal transduction pathway in a specific interaction between rice (Oryza sativa) and its bacterial pathogen, Xoo (Xanthomonas oryzae pv. oryzae). Constitutive expression of OsEREBP1 in rice driven by maize ubiquitin promoter did not affect normal plant growth. Microarray analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 67 publications
3
92
0
Order By: Relevance
“…Seed-priming with MJ and PB was found to increase AO activity in drought-sensitive genotype which may improve drought tolerance ability of the genotype. On the contrary, we observed SA to decrease AO activity by 45% in the drought-sensitive genotype ( Figure 4 ), which might be acting as antagonist (Jisha et al, 2015). A positive correlation between TPC and AO activity has been reported earlier to impart abiotic stress tolerance in plants (Trust et al, 2005; Rao et al, 2013).…”
Section: Discussionmentioning
confidence: 71%
“…Seed-priming with MJ and PB was found to increase AO activity in drought-sensitive genotype which may improve drought tolerance ability of the genotype. On the contrary, we observed SA to decrease AO activity by 45% in the drought-sensitive genotype ( Figure 4 ), which might be acting as antagonist (Jisha et al, 2015). A positive correlation between TPC and AO activity has been reported earlier to impart abiotic stress tolerance in plants (Trust et al, 2005; Rao et al, 2013).…”
Section: Discussionmentioning
confidence: 71%
“…LOXs‐activated pathways involve JA and abscisic acid signalling, thereby priming the rice plants for enhanced survival under abiotic or biotic stress conditions (Jisha et al . ). In this study, GSH2 , GSHU35 , LOX and HO1 were found to be differentially methylated, but accompanied with increased transcripts with Aza under Cd stress (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…LOX encoding an LOX (EC 1.13.11.1) catalyses oxygenation of fatty acids to their hydroperoxy derivatives and is one of the key enzymes in octadecanoid pathway upstream controlling jasmonic acid (JA) biosynthesis (Gardner 1991). LOXs-activated pathways involve JA and abscisic acid signalling, thereby priming the rice plants for enhanced survival under abiotic or biotic stress conditions (Jisha et al 2015). In this study, GSH2, GSHU35, LOX and HO1 were found to be differentially methylated, but accompanied with increased transcripts with Aza under Cd stress ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…EREBP was reported to confer biotic and abiotic stress tolerance in rice (Jisha et al, 2015). Serine/threonine protein kinases and receptor-like serine/threonine protein kinases have been associated with the early stage of plant defense.…”
Section: Discussionmentioning
confidence: 99%